2020
DOI: 10.1111/eva.12941
|View full text |Cite
|
Sign up to set email alerts
|

A river runs through it: The causes, consequences, and management of intraspecific diversity in river networks

Abstract: Rivers are fascinating ecosystems in which the eco‐evolutionary dynamics of organisms are constrained by particular features, and biologists have developed a wealth of knowledge about freshwater biodiversity patterns. Over the last 10 years, our group used a holistic approach to contribute to this knowledge by focusing on the causes and consequences of intraspecific diversity in rivers. We conducted empirical works on temperate permanent rivers from southern France, and we broadened the scope of our findings u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 163 publications
2
65
0
Order By: Relevance
“…However, both summer- and winter-run timing alleles have been detected in inland migrating populations and appear to be more strongly associated with arrival timing at spawning grounds rather than ocean migration timing [ 46 ]. Fragmentation of aquatic corridors and removal of natural barriers to migration have been implicated in the deviation of this genotypic–phenotypic association, indicating the importance of landscape connectivity for maintenance of run timing life histories [ 47 , 49 , 51 , 52 ]. Disruption to gene flow by barriers, therefore, could significantly impact the distribution of adaptive genetic variation underlying diverse migratory phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…However, both summer- and winter-run timing alleles have been detected in inland migrating populations and appear to be more strongly associated with arrival timing at spawning grounds rather than ocean migration timing [ 46 ]. Fragmentation of aquatic corridors and removal of natural barriers to migration have been implicated in the deviation of this genotypic–phenotypic association, indicating the importance of landscape connectivity for maintenance of run timing life histories [ 47 , 49 , 51 , 52 ]. Disruption to gene flow by barriers, therefore, could significantly impact the distribution of adaptive genetic variation underlying diverse migratory phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of D ist N et and R esist N et for increased automation also serves to encourage large-scale comparative riverscape studies involve variation among species in spatial or temporal trends, the results of which could vary substantially as a function of trait synergism or life histories (Comte et al 2014, McManamay and Frimpong 2015, Troia et al 2019). While rare, such intraspecific studies have implicated ongoing evolution within dendritic networks, while testing specific ecological questions (Fourtune et al 2016, Pilger et al 2017, Paz-Vinas et al 2018, Blanchet et al 2020). For example: Why do some species exhibit greater intraspecific variation in functional/ morphological attributes than do co-occurring species?…”
Section: Discussionmentioning
confidence: 99%
“…This in turn promotes asymmetric gene flow and a source-sink metapopulation structure (Campbell Grant et al 2007). Consequently, a prevailing trend is for a downstream increase in allelic diversity (Paz-Vinas and Blanchet 2015, Paz-Vinas et al 2015, Blanchet et al 2020), whereas unique genetic variation is most often retained within more peripheral headwater populations (Morrissey and De Kerckhove 2009, Chiu et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the evolutionary consequences of the network structure on the intraspecific genetic diversity are less well understood, even though one could apply the same approaches to study them. Comparative studies focusing on the effect of riverine network structures on intraspecific genetic diversity are still rare (Blanchet et al, 2020;Brauer et al, 2018;Fourtune et al, 2016), but generally show an increase in diversity in more downstream parts of the network ("downstream increase in intraspecific genetic diversity" (DIGD); . Importantly, these studies highlight that various processes can lead to such empirically observed patterns (Blanchet et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies focusing on the effect of riverine network structures on intraspecific genetic diversity are still rare (Blanchet et al, 2020;Brauer et al, 2018;Fourtune et al, 2016), but generally show an increase in diversity in more downstream parts of the network ("downstream increase in intraspecific genetic diversity" (DIGD); . Importantly, these studies highlight that various processes can lead to such empirically observed patterns (Blanchet et al, 2020). In parallel, theoretical models that address the effect of spatial connectivity of riverine networks on genetic variation (Morrissey & de Kerckhove, 2009;, on evolution of dispersal (Henriques-Silva et al, 2015), and emergence of neutral genetic structure (Fronhofer & Altermatt, 2017;Stokes & Perron, 2020;Thomaz et al, 2016) have demonstrated that dispersal along riverine networks has a direct imprint on the genetic structure and diversity of the inhabiting organisms.…”
Section: Introductionmentioning
confidence: 99%